Redox signals at the ER–mitochondria interface control melanoma progression. (15th July 2019) - Zhang, Xin; Gibhardt, Christine S; Will, Thorsten; Stanisz, Hedwig; Körbel, Christina; Mitkovski, Miso; Stejerean, Ioana; Cappello, Sabrina; Pacheu‐Grau, David; Dudek, Jan; Tahbaz, Nasser; Mina, Lucas; et al.
Abstract: Reactive oxygen species (ROS) are emerging as important regulators of cancer growth and metastatic spread. However, how cells integrate redox signals to affect cancer progression is not fully understood. Mitochondria are cellular redox hubs, which are highly regulated by interactions with neighboring organelles. Here, we investigated how ROS at the endoplasmic reticulum (ER)–mitochondria interface are generated and translated to affect melanoma outcome. We show that TMX1 and TMX3 oxidoreductases, which promote ER–mitochondria communication, are upregulated in melanoma cells and patient samples. TMX knockdown altered mitochondrial organization, enhanced bioenergetics, and elevated mitochondrial‐ and NOX4‐derived ROS. The TMX‐knockdown‐induced oxidative stress suppressed melanoma proliferation, migration, and xenograft tumor growth by inhibiting NFAT1. Furthermore, we identified NFAT1‐positive and NFAT1‐negative melanoma subgroups, wherein NFAT1 expression correlates with melanoma stage and metastatic potential. Integrative bioinformatics revealed that genes coding for mitochondrial‐ and redox‐related proteins are under NFAT1 control and indicated that TMX1, TMX3, and NFAT1 are associated with poor disease outcome. Our study unravels a novel redox‐controlled ER–mitochondria–NFAT1 signaling loop that regulates melanoma pathobiology and provides biomarkers indicative of aggressive disease. Synopsis: How reactive oxygen species (ROS) and mitochondrial contact sites to neighboring organelles affect cancer pathobiology remains unresolved. Here, endoplasmic reticulum (ER)‐mitochondria junctions are shown to promote aggressive behavior of melanoma via a ROS‐NFAT1 signaling loop. A video of this synopsis is availablehere . TMX1/3 oxidoreductases and transcription factor NFAT1 are upregulated in aggressive melanoma. TMX1/3 depletion disrupts ER‐mitochondria contacts and results in oxidative stress. Increased ROS inhibits NFAT1 nuclear translocation and cancer gene expression via oxidation of calcineurin. TMX1/3 depletion decreases melanoma proliferation and invasion in vitro and in xenograft experiments in vivo . Abstract : Melanoma growth is maintained by ER‐mitochondria communication and a TMX1/3‐ROS‐NFAT1 signaling axis.